Ecuaciones delictivas: artefactos, ambages, poemas plagiados, iconogénesis - Jorge Monteleone (Cuadernos LIRICO)
The endless poetic legacy of Nicanor Parra starts with the antipoetry and, in parallel, dissolves the figure of the self, to be substituted by a succession of masquerades: the neutral subject, the madman, and the pragmatic poet bricoleur that accompanies the dissolution of identity. The creation of the artefacts is the first symptom of an outbreak which pursues an increasing process of spatialization which goes from his visual poems to the objectual poems, that are, in their way, a tribute to Duchamp´s readymade. The combinatory praxis of Nicanor Parra´s poetic art and his artefacts show continuities with the work of three Argentine poets which belong to three generations: César Fernández Mofreno´s ambages, Esteban Peicovich´s poemas plagiados, and Mario Ortiz´ Tratado de Iconogénesis. The liberating character of Nicanor Parra´s poetic practices extend their revolutionary legacy to the XXI Century in written poetry in Spanish language.